2002
DOI: 10.3354/meps238187
|View full text |Cite
|
Sign up to set email alerts
|

Diets of walleye pollock Theragra chalcogramma in the Doto area, northern Japan: ontogenetic and seasonal variations

Abstract: Seasonal, ontogenetic and bathymetric variations of diet were examined for walleye pollock Theragra chalcogramma based on a total of 6666 fish collected off the southeastern coast of Hokkaido Island, northern Japan (Doto area) during 1989 to 2000. Walleye pollock depended exclusively (> 99%) on pelagic prey and showed a clear ontogenetic dietary shift: smaller fish depended mainly upon mesozooplankton such as Neocalanus cristatus and Euphausia pacifica, and larger fish preyed upon pollock (cannibalism), myctop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
3
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 49 publications
5
70
3
1
Order By: Relevance
“…pacifica even if that inhabit in the same Oyashio region [27] from that in Neocalanus copepods. Target strength estimated by using g and h in C. finmarchicus (open circles numbered 4 and 5) and C. hyperboreus (open circles numbered 6 and 7)…”
Section: Discussionmentioning
confidence: 99%
“…pacifica even if that inhabit in the same Oyashio region [27] from that in Neocalanus copepods. Target strength estimated by using g and h in C. finmarchicus (open circles numbered 4 and 5) and C. hyperboreus (open circles numbered 6 and 7)…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the strikingly high phytoplankton biomass observed at Station YB-1, where a high concentration of prymnesiophytes and high water temperature (>10 C) were observed in the euphotic zone, might have arisen from low grazing pressure (Figures 2 and 7). Several studies have reported that phytoplankton size composition and biomass are controlled by zooplankton grazing [Malone and Chervin, 1979;Burkill et al, 1995;Han and Furuya, 2000;Chiba and Saino, 2002;Yamamura et al, 2002]. Hiromi [1996] also found that grazing by zooplankton heavily depressed the phytoplankton biomass and productivity in Tokyo Bay.…”
Section: Size-fractionated Chlorophyll a And Primary Productivitymentioning
confidence: 99%
“…In the ecosystem of the Oyashio region, large calanoid copepods are important constituents of zooplankton comprising 80-90% of the zooplankton biomass (Vinogradov, 1970;Ikeda et al, 2008). These calanoid copepods are major prey for pelagic fishes (Takeuchi, 1972;Taka et al, 1982;Odate, 1994;Yamamura et al, 2002), marine mammals (Nemoto, 1963) and sea birds (Hunt et al, 1998), and are therefore regarded as key organisms in this region. In terms of biomass in the Oyashio region, Neocalanus cristatus is the most abundant copepod, followed by Eucalanus bungii (Ikeda et al, 2008).…”
Section: Introductionmentioning
confidence: 99%